2022
DOI: 10.24093/awej/vol13no2.29
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Effect of Translation on Improving Reading Comprehension among Female Arabic Learners of English as Foreign Language

Abstract: Translation has been one of the most commonly used strategies in learning an additional language. Although there is not a consensus on the usefulness of translation as a language learning strategy, the relevant literature indicated that it could contribute to the learning process when used purposefully and meaningfully. The present study aimed to explore the role of translation in supporting the language learning process by adopting an experimental design to reveal whether engaging in translation practice coul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…To facilitate reading English texts among EFL students in Taif University, Alaboud (2022) used translation as an effective strategy with the experimental group students. Venegas (2019) case study on a fifth-grade student participated in literature circles revealed that literature circles can foster students' socioemotional and academic learning.…”
Section: Reading Comprehension Difficultiesmentioning
confidence: 99%
“…To facilitate reading English texts among EFL students in Taif University, Alaboud (2022) used translation as an effective strategy with the experimental group students. Venegas (2019) case study on a fifth-grade student participated in literature circles revealed that literature circles can foster students' socioemotional and academic learning.…”
Section: Reading Comprehension Difficultiesmentioning
confidence: 99%